Raden Soedarsono dalam Revolusi Fisik di Kota Jambi 1945-1949 - Adam Abdurrahman Brilliant; Etmi Hardi (Lembaga Yasin AlSys, 2026)
The Jambi Residency held a strategic role in the Indonesian National Revolution (Revolusi Fisik, 1945–1949), particularly in maintaining political authority, organizing military resistance, and controlling vital economic assets, yet narratives about key local actors remain relatively marginalized in national historiography. This study aimed to examine the multidimensional role of Raden Soedarsono in the Physical Revolution in Jambi by analyzing his integrated involvement in civil administration, military affairs, and the management of the petroleum industry. Using the historical research method, which includes heuristics, source criticism, interpretation, and historiography, this study analyzed archives, family documents, museum collections, and oral testimonies to reconstruct Soedarsono’s activities and influence. The findings show that Raden Soedarsono played a central role as Resident of Jambi, Titulair Lieutenant Colonel, and Director of PERMIRI (Perusahaan Minyak Republik Indonesia), with active involvement in political and military decision-making, coordinating the management of oil refineries to support the logistical needs of the Republic of Indonesia, including fuel supplies for AURI (the Indonesian Air Force), and implementing a scorched earth (bumi hangus) policy at the Kenali Asam oil refinery on 29 December 1948 to prevent the reappropriation of strategic assets by the Dutch. This scorched earth policy significantly weakened Dutch economic capacity in Jambi and represented a form of strategic sacrifice for national sovereignty. The study concludes that Soedarsono’s integrative leadership model, which combined civil, military, and economic authority, was crucial for sustaining the revolutionary struggle at the regional level. His leadership legacy offers important lessons on resource sovereignty, ethical leadership, and the significance of local narratives in national historiography, while also underscoring the need to decentralize historical writing beyond Java-centric perspectives and enriching understanding of regional resistance dynamics and technocratic populism in Indonesia’s independence revolution.